Trade study to select best alternative for cable and pulley simulation for cranes on offshore vessels. Issue 2 (2nd August 2019) - Fotland, Gaute; Haskins, Cecilia; Rølvåg, Terje
Abstract: Cranes on offshore vessels are subjected to crane dynamics, structural couplings to the vessel, and environmental influence by waves and currents. The recent trend has been to use larger cranes on smaller vessels, which makes the lifting operation more complex and potentially dangerous. The use of digital twins (DTs) is emerging as one way to enable safer operations, real‐time simulation, and maintenance prediction. On offshore vessels, a DT can monitor the lifting operation to create a safer work environment. The SPADE (stakeholders, problem formulation, alternatives, decision making, and evaluation) model has been used as a framework toward the creation of a DT of cranes on offshore vessels. Several cases involving simulation of cranes revealed the lack of an adequate simulation of cable and pulleys suitable for use in a DT. The simulation is important for accurate results and for implementation in control systems. A trade study was performed to determine a numerical method adequate for cable and pulley simulation. The trade study identified the absolute nodal coordinate formulation in the framework of arbitrary Lagrangian–Eulerian as a promising numerical formulation.